Traffic Accident Rates by Transportation Mode on the National Road Between Pontianak and Sintang Regency - Betty, Klara Trianisa; Mayuni, Siti; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2025)
As the capital city of Kalimantan Barat, Pontianak serves as a center for government, trade, industry, and services. This role contributes to high land transportation mobility between Pontianak and Sintang Regency, increasing vehicle volume on the national road connecting the two regions. Consequently, the traffic accident rate on this road segment is relatively high and involves various types of vehicles. This research analyzes the traffic accident rate based on transportation modes to formulate mitigation strategies. The analysis includes categorizing accident characteristics and calculating accident rates based on the incident number and vehicle types. The findings indicate that motorcycles account for the highest number of traffic accidents, whereas buses have the lowest accident rate. The road segment with the highest accident rate is the Tebelian "“ Sintang Limits section, with a Rate of Accidents (RA) of 0,642 in 2023. Additionally, motorcycles recorded the highest accident rate on the same road segment, with an RA of 1,101 in 2023. of the road segment length influences the accident rate, where longer road sections tend to have lower accident rates despite a high number of accidents. Mitigation efforts include improving road infrastructure, enhancing traffic safety facilities, and increasing public awareness of safe driving practices.